(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
Railway platforms are often challenging to navigate for elderly and differently-abled passengers, especially during train arrivals and departures. This project proposes an Automatic Platform Bridge System designed to provide safe and convenient crossing at railway stations. The system integrates IR sensors to detect approaching trains, enabling the bridge to respond automatically to real-time conditions. DC motors are employed to control the movement of the bridge, allowing smooth and reliable opening and closing without manual intervention. LED indicators provide visual alerts to passengers, signaling when it is safe to cross or when train movement is imminent. The system architecture ensures synchronization between train detection and bridge operation, preventing accidents and unauthorized access during unsafe periods. Data from the sensors is continuously monitored to facilitate fail-safe operations, ensuring the bridge remains stationary in emergency situations. The design emphasizes low-cost, energy-efficient components for scalability and ease of implementation in small to medium railway stations. By automating bridge operation, the system reduces reliance on human operators, minimizes operational delays, and enhances platform safety. The proposed solution demonstrates the integration of IoT, sensor technology, and automation for practical applications in railway infrastructure. Experimental results indicate that the system responds promptly to train detection, maintains stability during bridge movement, and provides clear visual signaling to passengers. This approach improves accessibility, enhances passenger safety, and promotes efficient station management. The system can be further extended with remote monitoring and additional safety features for large-scale railway networks